Utilization of Assisted Hatching Techniques to Enhance Embryo Implantation - Arie Febretrisiana; Fitra Aji Pamungkas (Indonesian Center for Animal Research and Development, 2017)
Gestation is the main goal for in vitro fertilization. The embryo that has been developed outside the body will be transferred directly into uterus leading to the process of hatching, implantation, and pregnancy. However, approximately 85% of embryos that have been transferred were failed to implant and it might be caused by hatching failure. Hatching is the process of releasing embryo from zona pellucida. If this process does not occur, it will cause pregnancy failure. Assisted hatching is a mechanism that dealing with thinning, slicing or artificially making holes in the zona pellucida to improve hatching. The process can be applied both in fresh or frozen embryos. This review describes various methods in assisted hatching such as enzymatic, chemical, mechanical, and laser beam as well as their advantages and disadvantages. Generally, some researches show that the technology of assisted hatching can improve the percentage of hatching and implantation of the embryo. However, in spite of the benefits, there are such weaknesses find in the zona pellucida of the embryo that has been manipulated such as toxic hazard medium, the risk of damage to the blastomeres or monozygotic twinning. Therefore, it is advisable to perform assisted hatching in certain cases that tends to face obstacles during the process of hatching such factors as age, embryo quality, the thickness of the zona pellucida and the number of failures in the in vitro fertilization program.